Prognostic significance of osteopontin expression in non-small-cell lung cancer: A meta-analysis - ZOU, XUE-LIN (Mol Clin Oncol, 2015)
Osteopontin (OPN) plays an important role in the progression and metastasis of cancer. However, the role of OPN as a prognostic factor in non-small-cell lung cancer (NSCLC) remains controversial. The aim of this study was to investigate the association between OPN expression and prognosis in patients with NSCLC using a meta-analysis. Based on PubMed, Ovid Medline, Embase, ISI, ScienceDirect and SpringerLink databases, related articles published prior to January, 2013 were collected. A meta-analysis was conducted to investigate the association of OPN expression with overall survival (OS) and progression-free survival (PFS) in patients with NSCLC. Hazard ratio (HR) with 95% confidence interval (CI) was used to assess the strength of this association. A total of 6 studies, including 776 patients, were found to be eligible for the meta-analysis. No heterogeneity was observed in OS or PFS, whereas low OPN expression was found to be correlated with better OS (HR=0.57, 95% CI: 0.46–0.70) and PFS (HR=0.62, 95% CI: 0.49–0.77). This meta-analysis demonstrated an association of OPN with poor prognosis in NSCLC patients. However, prospective studies are required to confirm these findings.